Actinium-225-PSMA-617 treatment in a patient with advanced prostate cancer causes secondary myelofibrosis: a case report and literature review - Wang, Ziye; Tang, Wen; Liu, Mingwen; Xie, Zhifei; Li, Yi; Du, Jiang; Wu, Tao (Frontiers in Medicine, 2025)
Advanced prostate cancer (PCa) is still an incurable disease. Still, the field of PSMA-targeted radioligand therapy is developing rapidly and is playing an increasingly important role in the treatment of advanced Pca in the future. As an α -particle emitter, Ac-225 shows a potent killing ability for tumor cells due to its short range and high energy deposition in the tumor micrometastasis focus. However, the secondary myelofibrosis (SMF) associated with Ac-225-PSMA-617 treatment is a significant concern. We present a case of metastatic castration-resistant prostate cancer (mCRPC) who developed pancytopenia following the Ac-225-PSMA-617 treatment period, a bone marrow biopsy confirmed SMF and remained uncorrected after multiple component transfusions and symptomatic supportive therapy. Ac-225-PSMA-617 has demonstrated promising therapeutic efficacy in the management of advanced PCa; however, the potential risks associated with SMF necessitate careful consideration. Through comprehensive analysis of this clinical case and comparative evaluation with the existing literature, this study highlights the need to balance clinical benefit with increased vigilance for treatment-related adverse events.